2017
DOI: 10.1590/198053144299
|View full text |Cite
|
Sign up to set email alerts
|

O “teto de vidro” na França: o setor público é mais igualitário que o setor privado?

Abstract: RÉSUMÉ Cet article aborde le sujet des femmes cadres supérieures en

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…These inequalities are present in several countries and economic sectors, such as among private sector executives in France (Marry & Pochic, 2017) and male and female engineers in Brazil (Lombardi, 2006). In the Brazilian public sector, case studies carried out in universities and public bodies found patterns of salary and hierarchical inequalities and documented female strategies to overcome the glass ceiling and reach command positions (Barbosa & Oliveira, 2021).…”
Section: Gender Inequalities In Public Administrationmentioning
confidence: 99%
“…These inequalities are present in several countries and economic sectors, such as among private sector executives in France (Marry & Pochic, 2017) and male and female engineers in Brazil (Lombardi, 2006). In the Brazilian public sector, case studies carried out in universities and public bodies found patterns of salary and hierarchical inequalities and documented female strategies to overcome the glass ceiling and reach command positions (Barbosa & Oliveira, 2021).…”
Section: Gender Inequalities In Public Administrationmentioning
confidence: 99%
“…Essas desigualdades estão presentes em diversos países e setores econômicos, como entre executivos do setor privado na França (Marry & Pochic, 2017) e engenheiras e engenheiros no Brasil (Lombardi, 2006). No setor público brasileiro, estudos de caso realizados em universidades e órgãos públicos encontraram padrões de desigualdades salariais e hierárquicas, assim como documentaram estratégias femininas para driblar o teto de vidro e alcançarem postos de comando (Barbosa & Oliveira, 2021).…”
Section: Desigualdades De Gênero Na Administração Públicaunclassified
“…Other research portrays the glass ceiling, such as Vaz (2013), who discusses the glass ceiling in public service careers in Brazil and Marry and Pochic (2017), who do the same in France. Although they are more egalitarian in terms of entry-level positions, in both cases few women occupy upper management due to stereotypical gender discrimination.…”
Section: Introductionmentioning
confidence: 99%